TIPOLOGI PARTISIPASI POLITIK PEMILIH LAKI-LAKI DI KABUPATEN BOGOR BERDASARKAN PENGGUNAAN SUMBER INFORMASI POLITIK - Jayawinangun, Roni; Valdiani, Dini (Interaksi: Jurnal Ilmu Komunikasi, 2020)
In nowdays context, the community political participation has slightly changed as a result of technological development. In 2018, our regional election had failed to achieve minum target of political participation level that had been given by the Indonesian government. The government was targeting 77.5 percent but in the reality the society participation level only reached 73.24 percent due to the low level of participation from male voters. This research is conducted in order to identify male voters typology in Bogor Regency based on their utilization of political information sources or media. Quantitative method was used as metodological approach, 200 male voters were taken as research sampel by using quota samping based on their electoral district, and Chi-Square Automatic Interaction Detector (CHAID) was used as data analysis. This research finds that television and internet are the most frequently used media meanwhile, campaign props and television are the most trusted source of political information. The typology of male voters with the highest percentage in Bogor Regency is apathetic voters (34%) followed by naive (29.5%), alienated (19%) and loyal voters (17.5%).